2008
DOI: 10.1038/ajh.2007.10
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relationship Between Ambulatory Arterial Stiffness Index and Glomerular Filtration Rate in Arterial Hypertension

Abstract: AASI is inversely related to GFR in arterial hypertension. This may help to explain the increased CV risk associated with mild-to-moderate renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 27 publications
(44 reference statements)
6
29
0
Order By: Relevance
“…25 More recently, Mulè et al found that AASI was inversely related to GFR in a group of 143 untreated hypertensive subjects with serum creatinine <1.5 mg/dL. 26 Other authors have found similar correlations with creatinine clearance estimated from serum creatinine 24 or with GFR computed from the scintigraphic determination of the technetium-99m diethylenetriaminepentaacetic acid uptake within the kidneys, by the Gates method. 25 There is less experience with Sym-AASI but in a recent report Sym-AASI showed a significant relationship with creatinine clearance, serum creatinine, and eGFR estimated using Modification of Diet in Renal Disease-4 equation.…”
Section: Discussionmentioning
confidence: 88%
“…25 More recently, Mulè et al found that AASI was inversely related to GFR in a group of 143 untreated hypertensive subjects with serum creatinine <1.5 mg/dL. 26 Other authors have found similar correlations with creatinine clearance estimated from serum creatinine 24 or with GFR computed from the scintigraphic determination of the technetium-99m diethylenetriaminepentaacetic acid uptake within the kidneys, by the Gates method. 25 There is less experience with Sym-AASI but in a recent report Sym-AASI showed a significant relationship with creatinine clearance, serum creatinine, and eGFR estimated using Modification of Diet in Renal Disease-4 equation.…”
Section: Discussionmentioning
confidence: 88%
“…AASI and its related slope have been shown to predict outcome, 5,7,8,29 as well as target organ damage. 6,30 However, the importance of these parameters as measures of arterial properties has been questioned by downplaying the role of AASI as a genuine correlate of arterial stiffness 31,32 because of its strong dependence on age, gender, 31,32 pulse pressure 32 and nocturnal BP decline. 3,25, 32 We report here that the slope-related indices, AASI, AASI(bisect), Slope(bisect) and BPVR, all predict mortality to a certain extent, and that the indices derived from the proper symmetric regression 8 and the calculated BPVR, tend to predict even better.…”
Section: Discussionmentioning
confidence: 99%
“…AASI is defined as 1 minus the DBP-on-SBP regression slope, the latter obtained using a standard asymmetric regression of DBP-on-SBP readings during a 24-h ambulatory BP monitoring session. 7 The clinical relevance of AASI is suggested by its cross-sectional correlation with preclinical target-organ damage [16][17][18] and its predictive value for future cardiovascular morbidity and mortality, [19][20][21][22] although the superiority of AASI over more widely accepted surrogate measures of arterial stiffness such as 24-h pulse pressure 23 has not been established. 24,25 Some methodological drawbacks of AASI need to be considered, however.…”
Section: How To Measure Sbp-on-dbp Regression Slope?mentioning
confidence: 99%